UNDERSTANDING LAND-USE CHANGE DRIVING FORCES OF SUB-URBAN AREA IN BANTUL REGENCY, YOGYAKARTA - Simamora, Obed Milton (FIA UB, 2013)
Abstract: Understanding Land-Use Change Driving Forces Of Sub-Urban Area In Bantul Regency, Yogyakarta. In sub-urban areas, the conversion of agriculture land to housing land-use is high annually. By allowing the trend continues the long term impact will be a gradual loss of farmland to a major extent. This research investigated land-use change during 2000 until 2012 of two sub-districts in Bantul Regency as a study case. By using remote-sensing images, land-use maps were created and analyzed. Other essential documents and interview in qualitative approach provided data to investigate the driving forces. This study found that the areas closer to the city experienced rapid and wide changed of wetland agriculture than rural areas. The most frequent and large alteration was from wetland agriculture to housing. The local regulations and population growth were among the drivers. It is recommended to determine land-use policy of other sub-urban areas for anticipating. Keywords: sub-urban area, land-use change Â Abstrak: Understanding Land-Use Change Driving Forces Of Sub-Urban Area In Bantul Regency, Yogyakarta. Pada kawasan sub-urban, perubahan tata guna tanah (TGT) dari pertanian menjadi non-pertanian sangat tinggi tiap tahunnya, yang mengakibatkan hilangnya tanah pertanian secara signifikan. Riset ini meneliti perubahan TGT periode 2000-2012 di dua kecamatan di Kabupaten Bantul. Dengan menggunakan citra penginderaan jauh, dibuat peta perubahan TGT dan dianalisa. Dokumen lainnya dan wawancara dengan pendekatan kualitatif dilakukan untuk mengetahui faktor pendorong perubahan itu (driving forces). Hasil temuan menunjukkan bahwa daerah yang lebih dekat dengan kota mengalami perubahan yang lebih cepat dan lebih luas dari tanah pertanian menjadi non-pertanian. Peraturan daerah dan pertumbuhan penduduk ada di antara faktor pendorongnya. Direkomendasikan untuk menerbitkan peraturan daerah tentang pengaturan TGT sub-urban lainnya untuk antisipasi. Kata kunci: kawasan sub-urban, perubahan tata guna tanah